Three Against the Third Republic : Sorel, Barres and Maurras - Curtis, Michael, 1923- (Book collections on Project MUSE., 1959)
This volume is a comparative study of the political thought of three writers who, between 1885 and 1914, were leaders in the counterrevolutionary movement in France. Maurice Barres was a nationalistic conservative; Charles Maurras, a classic reactionary; and Georges Sorel, a moralist and syndicalist. Different though the three men were in their conception of political order, they were in common opposed to liberal democracy as a system of government and to most of the ideology and institutions of the Third Republic. Because of their impact on the generation that guided France before World War I, and because many of their attitudes foreshadow later totalitarian programs, Sorel, Barres and Maurras have a significant place in any assessment of modern European political history. Originally published in 1959. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.